Rancang Bangun E-Library Berbasis SLIM Meningkatkan Literasi Mahasiswa Pada Perpustakaan Stmik Indragiri Pekanbaru - Anshori, Ikhwan; Sahrun, Nori (Jurnal Sistem Informasi Dan Informatika, 2025)
E-library is one proof of the development of technology in the 4.0 era. Although E-library as a new breakthrough in conventional libraries continues to develop, it does not rule out the possibility that these developments are always maximally utilized, as is the case with the library at STMIK Indragiri Pekanbaru which still utilizes a conventional library. This is the cause of low literacy at STMIK Indragiri Pekanbaru, because it is still considered uninteresting and boring. The methods used in this research are Waterfall and quantitative, which are methods used in developing and describing a software through several sequential processes, flowing from top to bottom by passing through several phases in the use of SliM 9 Bulian services in improving student digital literacy. Strengthening and mentoring are also well implemented to provide understanding for the STMIK Indragiri Pekanbaru academic community regarding features, book management, book borrowing, and book returns. The results of this study conclude that by optimizing the STMIK Indragiri Pekanbaru library into an E-Library provides many benefits and various positive impacts for library managers and users.